2018
DOI: 10.1080/24740527.2018.1479842
|View full text |Cite
|
Sign up to set email alerts
|

A systematic review of strategies to improve appropriate use of opioids and to reduce opioid use disorder and deaths from prescription opioids

Abstract: Background: Abuse of prescription opioids is a serious problem in North America. Aims: The aim of this study was to conduct a systematic review of peer-reviewed and grey literature to examine existing strategies aimed at improving the appropriate use of prescription opioids and/or reducing the misuse, abuse, and diversion of these drugs. Methods: The following electronic databases were searched to September 2015 without language restrictions: MEDLINE, EMBASE, PsycINFO, and CINAHL; the grey literature was searc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
26
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(26 citation statements)
references
References 89 publications
(451 reference statements)
0
26
0
Order By: Relevance
“…Also lacking was the use of evidence to support the selection of intervention components in community opioid-related plans; thus, conclusions about which interventions constitute best practice in local plans cannot be made. Evidence supports several interventions aimed at reducing opioid or substance-related harms that were used in plans, including: supervised consumption services,130 131 needle and syringe programmes,132 overdose education and naloxone distribution,133 methadone maintenance or buprenorphine treatment134 and school-based strategies that address youth protective factors 135–137. Several plans included interventions that have been found ineffective (eg, Drug Abuse Resistance Education programmes)138 or have little evidence for effectiveness (eg, medication take-back programme) 139 140.…”
Section: Discussionmentioning
confidence: 99%
“…Also lacking was the use of evidence to support the selection of intervention components in community opioid-related plans; thus, conclusions about which interventions constitute best practice in local plans cannot be made. Evidence supports several interventions aimed at reducing opioid or substance-related harms that were used in plans, including: supervised consumption services,130 131 needle and syringe programmes,132 overdose education and naloxone distribution,133 methadone maintenance or buprenorphine treatment134 and school-based strategies that address youth protective factors 135–137. Several plans included interventions that have been found ineffective (eg, Drug Abuse Resistance Education programmes)138 or have little evidence for effectiveness (eg, medication take-back programme) 139 140.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, there is relatively little research to guide the design of campaigns for opioid-related topics and stigma ( National Academies of Sciences, Engineering, and Medicine, 2016 ). Furlan et al (2018) conducted a systematic review of the effectiveness of various strategies to reduce OUD and opioid overdose deaths and, based on limited evidence from five studies, found communication campaigns to be one of the most promising strategies.…”
Section: Introductionmentioning
confidence: 99%
“…Reviews of these campaigns have found evidence for small to moderate impacts on stigma-related knowledge, attitudes, and intended behavior, but also found that campaigns often failed to identify goals and objectives and did not reach the intended audiences in a sustained or adequately frequent manner ( Gronholm et al, 2017 ; NAS, 2016). However, there are few studies to guide the design of campaigns for opioid-related stigma ( Furlan et al, 2018 ; NAS, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…[26][27][28] Up to now, most efforts have been concentrated on studying the effects of strategies to reduce the use of opioid in patients already on chronic therapy. 29 Recently, mandatory prescription limits have been associated with a reduction of opioid use after elective surgeries. [30][31][32][33] However, our knowledge of the potential strategies is limited, and none are currently broadly applied as standard of care interventions.…”
Section: Open Accessmentioning
confidence: 99%